Evaluation of enhanced external counterpulsation with different modes on acute hemodynamic effects - Zhong, Yujia; Hao, Liling; Jia, Xue; Paek, Songrim; Tian, Shuai; Wu, Guifu (Frontiers in Physiology, 2025)
ObjectiveEnhanced external counterpulsation (EECP) is a noninvasive device for the treatment of cardiovascular diseases. However, there are minimal data regarding the effects of different EECP modes on acute hemodynamic changes, particularly blood flow redistribution. This study aimed to investigate the systemic hemodynamic effects during different EECP modes based on clinical trials and numerical analysis.MethodsFifteen patients with cardiovascular disease and 15 healthy subjects completed four and six EECP modes, respectively. These EECP modes changed the parameters, including counterpulsation pressure, start time, and counterpulsation frequency. Hemodynamic parameters in the aorta (AO), right femoral artery (RF), and right brachial artery (RB), including mean flow rate (FR), mean blood velocity (MV), peak systolic velocity (PSV), minimum diastolic velocity (MDV), and diastolic/systolic blood pressure ratio (D/S), were measured during EECP treatments. Meanwhile, the simulation of hemodynamic responses to different EECP modes based on a 0D-1D cardiovascular system model were conducted and compared with the clinical results.ResultsAs counterpulsation pressure increased, the FR and PSV of AO, the FR, MV, PSV, and MDV of RF, the FR, MV, and MDV of RB, and D/S increased in patients (all P < 0.05). The MV of RF, the FR, MV, PSV, and MDV of RB, and D/S of patients decreased significantly with increasing start time (all P < 0.05). For the increase of counterpulsation frequency, the FR, MV, and PSV of AO, the MV, PSV, and MDV of RF, and the FR and MV of RB significantly decreased in patients (all P < 0.05). For the health group, most patients’ results were similar. Multiple groups of pressure experiments indicated that 25–30 kPa significantly improved blood flow. The numerical results under different EECP modes were generally closely aligned with clinical measurements.ConclusionDifferent EECP modes induced different hemodynamic responses. Higher counterpulsation pressure, T wave start time, and 1:1 counterpulsation frequency are recommended to improve blood flow. Hemodynamic simulations prepare the way for the creation of virtual databases to obtain population-based strategies and then allow for precision-based strategies through individual modeling. The different hemodynamic responses to EECP modes provide theoretical guidance for the development of a patient-specific treatment strategy.